Clinical and Electroencephalographic Profile Of Children - Limbu, N; Paudel, BH; Thakur, D (Kathmandu University Medical Journal, 2015)
Background Reports on pediatric electroencephalogram of Nepalese patients are rare. Objective We aimed to study the relationship between provisional clinical and electrophysiological diagnoses of pediatric patients with documentation of demographic profiles, and type and frequency of the disorders/diseases. Methods Electroencephalographic reports of 634 children from 2006 to 2009 were analyzed at neurophysiology laboratory, department of Basic and Clinical Physiology, B. P. Koirala Institute of Health Sciences, Dharan, Nepal, retrospectively. Chi-Square test was applied after detail descriptive statistics. Results Male and female were 72.2 % (n=458/634) and 27.76 % (n=176/634) respectively. Most frequent EEG abnormality was seizure disorder (n=370, 59.39%), then febrile seizure (n= 94, 15.08%) and birth asphyxia with hypoxic-induced encephalopathy (n=68, 10.91%). Electroencephalogram showed significant epileptiform discharges in seizure disorder (p=0.001, OR= 2.26, 95 % CI= 1.61 to 3.18) and in cerebral palsy (p=0.049, OR=6.88, 95 % CI=0.89 to 145.95), specifically in 6 to 12 (p=0.001, OR=2.94, 95 % CI=1.43 to 6.06) and one to five (p=0.019) years, respectively. Electroencephalogram detected significantly less epileptiform discharges (p=0.001, OR=0.25, 95 % CI= 0.15 to 0.42) in febrile seizure specifically in 1 to 5 years (p=0.003, OR=0.16, 95 % CI= 0.04 to 0.63). Conclusion Predominant Electroencephalographic abnormality was seizure disorder, followed by febrile seizure and birth asphyxia with hypoxic-induced encephalopathy respectively. Electroencephalographic abnormality was highly associated with seizure disorder and cerebral palsy but was not associated with febrile seizure. DOI: http://dx.doi.org/10.3126/kumj.v11i2.12484 Kathmandu University Medical Journal Vol.11(2) 2013: 110-116